Pengaruh Efikasi Diri dan Hasil Belajar Praktek Kerja Industri terhadap Kesiapan Kerja Siswa Sekolah Menengah Kejuruan - Iskandar, Tia Halizah; Miranti, Mauren Gita; Sutiadiningsih, Any; Handajani, Sri (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
Data survey in the field in 2021 Dharma Wanita Gresik Vocational School, which implemented an apprenticeship program for all class XII students in culinary management as many as 28 students for four months, that is, less than 70% could be absorbed in the world of work. This shows that the goals of technical and vocational schools have yet to be realized, so there are still many students who get jobs that are not in accordance with their abilities in the catering field. This study aimed to determine the effect of self-efficacy on student work readiness, the effect of apprenticeship learning outcomes on student work readiness and the effect of self-efficacy and apprenticeship learning outcomes on student work readiness. This study used a quantitative descriptive method with a sample of 23 students with a sampling technique using purposive sampling. This study found that self-efficacy had a significant effect on students' work readiness with a t-count of 3,379 > t-table of 1,713, t-count of 2,417 < t-table of 1,713, and F-count of 10,616 > F-table of 4.24.